Determination of parents purchasing behaviour towards 'fun food' for their children among staff UiTM Campus Kota Kinabalu Sabah / Muhammad Saifullah Musadad Ahmad Tamizi - Ahmad Tamizi, Muhammad Saifullah Musadad; Abdul Rahman, Amal Nurul Ain; Ibnu Rasid, Mohd Shahrul Eshyan; Shasuddin, Muhammad Syaffiq; Osman, Noradilla (2014)
The purpose of this study is to determined as well as to identify the relationship between the variables of packaging and the children influences over parents purchasing behaviors towards the Fun Food product. This study is more focusing on the parents purchasing behavior towards Fun Food product for their children. Thus, this study is to identify on how well the packaging and the effect of the children influences could change the pattern of the parents in their purchasing. The criteria of the packaging is included the shape, colour, design and the characteristics on the packaging as well as the taste elements. Meanwhile, the children influence could also be one of the factors in parents purchasing behavior patterns towards Fun Food. The persuasion by their children attempts to exert influence'over their parents purchasing patterns in a repetitive way until their achieved their level of success by nagging. Thus, the results of this analysis can be used in find which variables are probably significant towards parents purchasing behavior in buying the Fun Food product. The outcome in the findings could give specific answer on the relationships occurs. The findings might be useful in marketers to find out more strategies in attracting children attention towards Fun Food in order to attract their parents.